O66: FLOW CYTOMETRIC AND RNA SEQUENCED UNCOUPLING OF TUMOUR-INFILTRATING LYMPHOCYTE CHECKPOINT EXPRESSION AND MISMATCH REPAIR STATUS IN COLORECTAL CANCER. (27th April 2021) - Zaborowski, A; Harmon, C; Duquette, D; Dyck, L; Lynch, L; Winter, D
Abstract: Introduction: Selection criteria for immunotherapy with checkpoint blockade in colorectal cancer are currently based on mismatch repair status. However, intra-tumoral T cell response varies among patients with the same MMR status. Inhibitory checkpoint expression on tumour-infiltrating lymphocytes in microsatellite stable and unstable CRC is unknown. Method: Flow cytometric analysis and single-cell RNA sequencing, using the 10x genomic platform, were performed ex vivo on tumour and uninvolved colonic tissue samples from patients undergoing surgical resection for colorectal cancer. Inhibitory checkpoint expression (PD-1) and functional status of isolated populations of TILs were analysed. Result: Conventional and unconventional tissue-resident T cells were enriched in tumour samples compared to uninvolved healthy colonic tissue. Upregulation of PD-1 expression on TILs was observed in all patients, however the % upregulation varied among those with the same MMR status. A proportion of MSS tumours were found to have high levels of PD-1 expression, while a subset of MSI tumours had low PD-1 expression. Functional studies of cytotoxicity demonstrated varying TIL production of IFNg, TNFa and amphiregulin in patients with the same MMR status. Conclusion: TIL profile (infiltration pattern, checkpoint expression and functional status) differs among patients with the same MMR status. A subset of 'hot' immunogenic MSS tumours exist that may respond to checkpoint blockade. Characterisation of TIL profile represents a more accurate method of selecting patients likely to derive benefit. Abbrev . CRC Colorectal cancer, MMR Mismatch repair, TIL Tumour-infiltrating lymphocytes, MSS Microsatellite stable, MSI Microsatellite unstable, IFNg Interferon-gamma, TNFa Tumour necrosis factor alpha Take-home message: A subset of immunogenic microsatellite stable colorectal tumours exist that may respond to checkpoint blockade. Mismatch repair status alone does not accurately predict response to immunotherapy.